Inequality in hospitalization due to non-communicable diseases in Sweden: Age-cohort analysis of the Uppsala Birth Cohort Multigenerational Study. (March 2021) - Gondek, Dawid; Ploubidis, George B.; Hossin, Muhammad Zakir; Gao, Menghan; Bann, David; Koupil, Ilona
Abstract: We aimed to investigate cohort differences in age trajectories of hospitalization due to non-communicable conditions, and if these varied by paternal socioeconomic position. We used the Uppsala Birth Cohort Multigenerational Study—including virtually complete information on medical diagnoses. Our sample constituted 28, 448 individuals (103, 262 observations). The outcome was five-year prevalence of hospitalization due to major non-communicable conditions in 1989–2008. The exposures were age (19–91), year-of-birth (1915–1929; 1938–1972), gender (man vs woman), and parental socioeconomic position (low, medium, and high). We used multilevel logit models to examine associations between exposures and the hospitalization outcome. Younger cohorts had a higher prevalence of hospitalization at overlapping ages than those born earlier, with inter-cohort differences emerging from early-adulthood and increasing with age. For instance, at age 40 predicted probability of hospitalization increased across birth-cohorts—from 1.2% (born in 1948-52) to 2.0% (born in 1963-67)—whereas at age 50 it was 2.9% for those born in 1938-42 compared with 4.6% among participants born in 1953-57. Those with medium and low socioeconomic position had 13.0% and 20.0% higher odds of experiencing hospitalization during the observation period, respectively—when age, year-of-birth and gender were accounted for. We found that no progress was made in reducing the socioeconomic inequalities in hospitalization across cohorts born between 1915 and 1972. Hence, more effective policies and interventions are needed to reduce the overall burden of morbidity—particularly among the most vulnerable. Highlights: What is already known on this subject? The evidence on trends in morbidity in Sweden is mainly cross-sectional and focused on individual conditions. Rates of various indicators of morbidity (e.g. poor mobility, psychological distress, disability) have increased over time. What this study adds. Successively younger birth cohorts had a higher prevalence of hospitalization, with differences emerging in early-adulthood. Those in medium and low parental socioeconomic position (vs high) had 13% and 20% higher odds of hospitalization. No progress was made in reducing the socioeconomic inequalities across cohorts born between 1915 and 1972.